Open access to scientific publications - an analysis of the barriers to change - Professor Bo-Christer Björk (Information Research: An International Electronic Journal)
One of the effects of the Internet is that the dissemination of scientific publications in a few years has migrated to electronic formats. The basic business practices between libraries and publishers for selling and buying the content have, however, not changed much. Scientists have in protest against the high subscription prices of mainstream publishers started Open Access (OA) journals and e-print repositories, which distribute scientific information freely. Despite widespread agreement among academics that OA would be the optimal distribution mode for publicly financed research results, OA channels still constitute only a marginal phenomenon in the global scholarly communication system. This paper discusses, in view of the experiences of the last ten years, the many barriers hindering a rapid proliferation of Open Access. The discussion is structured according to the main OA channels; peer-reviewed journals for primary publishing, subject-specific and institutional repositories for secondary parallel publishing. It also discusses the types of barriers, which can be classified as: legal framework, IT-infrastructure, business models, indexing services and standards, academic reward system, marketing and critical mass.